Improvement of gel properties of low salt surimi using low-dose l-arginine combined with oxidized caffeic acid. (June 2021) - Xiong, Zhiyu; Shi, Tong; Zhang, Wei; Kong, Yunfei; Yuan, Li; Gao, Ruichang
Abstract: The combined effects of l -arginine (Arg) and oxidized caffeic acid (OCF) treatment under different salt concentrations on gelling properties of bighead carp ( Aristichthys nobilis ) surimi gels were investigated. The results showed that the improvement of gel strength and water-holding capacity (WHC) of low-salt (0.5%) surimi gels could be obtained by adding Arg at various levels (0.1–0.4%) rather than OCF (0.1–0.9%, based on protein content). However, the gel strength and WHC of the low-salt surimi gel added with low-dose (0.1%) Arg alone were still far lower than that of regular-salt (3.0%) control. Whereas the significant improvements in low-salt surimi gels could be achieved when 0.1% Arg was combined with various levels of OCF, especially in combination with 0.5% OCF (LC-A-O). The water distribution in LC-A-O was markedly improved and its β-sheet structure content was significantly increased compared with the low-salt control ( P  < 0.05). Moreover, a denser and more uniform network structure of LC-A-O was obtained, which was probably due to much stronger and more intra-molecular cross-linking of proteins, via the formation of new adducts between OCF and surimi proteins. Hence, the combined treatment of Arg and OCF showed a potential for improving the gel properties of low-salt surimi. Highlights: The combination of Arg and OCF increased β-sheet content of the surimi protein. Arg increased protein solubility, which helped OCF react with proteins. Protein-OCF adducts help to improve the low salt surimi gel properties. Arg and OCF played synergistic roles in enhancing low salt surimi gel properties.